O Cinema e a Grande Guerra (1914-1918): os filmes sob as perspectivas do regime estético das artes de Jacques Rancière e dromologia em Paul Virilio - Sousa Júnior, Maurício José de (2014)
The Great War (1914-1918) caused important changes in space and the sensory-motor apparatus of men. Technological advances and experiences of transformation of perception added to the war and cinema space articulate extremely rich interpretative possibilities. We understand these modifications as an aesthetic problem. From this, we make movies about the war of 1914-1918, object of our analysis. To this, approach the thought of Jacques Rancière, the concept of aesthetic regime of art and the visibilities brought by Paul Virilio, with the concept of dromologia .